2021
DOI: 10.1186/s12711-021-00606-5
|View full text |Cite|
|
Sign up to set email alerts
|

A theoretical derivation of response to selection with and without controlled mating in honeybees

Abstract: Background In recent years, the breeding of honeybees has gained significant scientific interest, and numerous theoretical and practical improvements have been made regarding the collection and processing of their performance data. It is now known that the selection of high-quality drone material is crucial for mid to long-term breeding success. However, there has been no conclusive mathematical theory to explain these findings. Methods We derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, it is unclear, how genetic parameters that were received from the QM or WM should be integrated into modern strategies of genetic evaluation. In any case, without controlled mating, the genetic progress in breeding programs will be slow ( Plate et al 2019b ; Du et al 2021a ). When using the QM and WM in populations with controlled mating, one should bear in mind that the genetic influence on a trait is likely to be overestimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear, how genetic parameters that were received from the QM or WM should be integrated into modern strategies of genetic evaluation. In any case, without controlled mating, the genetic progress in breeding programs will be slow ( Plate et al 2019b ; Du et al 2021a ). When using the QM and WM in populations with controlled mating, one should bear in mind that the genetic influence on a trait is likely to be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The situation for the honeybee can be ameliorated by the use of artificial insemination or isolated mating stations, which provide a certain degree of paternal pedigree information ( Bienefeld et al 1989 ; Brascamp and Bijma 2014 ; Uzunov et al 2017 ). But although it has been shown that these strategies substantially enhance genetic response ( Plate et al 2019b ; Du et al 2021a ), many honeybee populations are still bred without or with incomplete mating control ( Andonov et al 2019 ; De la Mora et al 2020 ; Maucourt et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio between maternal and direct genetic gain was also only slightly influenced by the mode of genetic In contrast, earlier studies have shown that this ratio can be heavily influenced by the mating strategy of the breeding programme (Du et al, 2021a;Kistler et al, 2021;Plate et al, 2019b). Furthermore, Bernstein et al (2021) showed that the inclusion of genomic queen data into the BLUP evaluations shifts the breeding focus towards the maternal effects.…”
Section: Single-trait Selectionmentioning
confidence: 87%
“…Instead, both phenomena were consequences of incomplete phenotype records due to preselection strategies. Thus, in comparison with other factors that influence breeding success in honeybees, such as mating control (Du et al, 2021a; Plate et al, 2019b) or the inclusion of genomic data in the relationship matrix (Bernstein et al, 2021; Brascamp et al, 2018; Gupta et al, 2013), the use of correct genetic parameters in single‐trait selection appears secondary. The results clearly suggest that BLUP selection is a viable option in honeybee breeding, also for incipient breeding programmes where genetic parameters cannot yet be estimated with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the larvae from the observed patrilines differed in their ability to resist infections by M. plutonius suggests a paternally transmissible mechanism, which raises the prospect of breeding honey bee lineages resistant to this pathogen. Population genetics simulations and modelling studies have shown that controlled breeding of honey bees using high‐quality drones is beneficial for colonies because it increases breeding success (Du et al, 2021; Plate et al, 2019). Such a medication‐free approach is highly desirable, as there is currently no sustainable method in the beekeeping industry for combating EFB infection.…”
Section: Discussionmentioning
confidence: 99%